How Is The Legal Protection Against Royalty Of Performing Rights Of Music Or Song For Commercial Interests In Music Concerts In The City Of Gorontalo - Mohamad Ma'rif Yahya (Estudiante Law Journal, 2026)
The purpose of this research is to find out how the arrangement and implementation of the collection of music or song performing rights royalties at music concerts in the City of Gorontalo. Knowing how to overcome obstacles in collecting Royalty Performing Right music or songs at Music Concerts in the City of Gorontalo.  The type of research used in this research is empirical research, using data types consisting of primary data and secondary data. Data collection techniques are also carried out using interview, documentation and observation techniques. Then the data were analyzed descriptively using a qualitative approach. Legal Protection for Music or Song Royalties for Commercial Interests in Music Concerts in the Gorontalo Region has not been properly realized in accordance with Copyright Law No. 28 of 2014. This can be seen from statements or statements from several resource persons (Event Organizers) in Gorontalo. Where there is still a lack of knowledge of the public or users of music or songs commercially regarding the payment of Royalty Performing Right. This is due to the absence of a Collective Management Institution operating in the Gorontalo area and efforts to overcome obstacles in collecting performing rights royalties for music or songs for commercial purposes at music concerts in the Gorontalo City area, namely by increasing public awareness of royalties through socialization by collective management institutions, as well as establish a branch office of the Collective Management Institution in the Gorontalo Region so as to facilitate the collection and distribution of royalties to Creators.